2022
DOI: 10.3390/children9111631
|View full text |Cite
|
Sign up to set email alerts
|

The Trap of the COVID-19 Pandemic: Italian Adolescents Fare Well at First, Maybe Thanks to Protective Trait Expression

Abstract: Abundant research indicates that the COVID-19 pandemic has been negatively affecting mental health in adolescence. Few works, however, benefit from data from the same sample before and after the onset of the pandemic. The present longitudinal study involved a non-clinical group of 136 Italian adolescents (Mage = 16.3 years ± 1.08, 67% girls) to investigate their psychological response to the first lockdown and explore the role of a protective trait (i.e., Positivity) in moderating the effect of Intolerance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 64 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…Additional longitudinal studies about the impact of COVID-19 on adolescents and young adult Italian population suggest that the pandemic’s persistence over time may have had an impact on youth’s psychopathology, influencing the frequency, type, and complexity of mental health problems [ 7 , 8 ]. Furthermore, evidence revealed that the new generation of adolescents may express their discomfort through alternative-type symptoms rather than the expected “traditional” internalizing forms, including a higher problematic social media usage than peers before the pandemic [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional longitudinal studies about the impact of COVID-19 on adolescents and young adult Italian population suggest that the pandemic’s persistence over time may have had an impact on youth’s psychopathology, influencing the frequency, type, and complexity of mental health problems [ 7 , 8 ]. Furthermore, evidence revealed that the new generation of adolescents may express their discomfort through alternative-type symptoms rather than the expected “traditional” internalizing forms, including a higher problematic social media usage than peers before the pandemic [ 9 ].…”
Section: Introductionmentioning
confidence: 99%